2021
DOI: 10.1111/1477-8947.12242
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effect of energy consumption on different environmental indicators in the United States: The role of financial development and renewable energy innovations

Abstract: This study offers new insights into the relationship between energy consumption and environmental degradation in the United States by controlling for financial development, renewable energy innovations, economic expansion, and trade policy uncertainty over the period 1985:Q1 to 2014:Q4. Based on the flexible autoregressive distributed lag model, our findings show that energy consumption deteriorates the environment, while renewable energy innovations reduce CO2 emissions but has no significant effect on ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 69 publications
3
10
0
Order By: Relevance
“…Inflation worsens the financial system as predicted by most theories. These findings are consistent with Lahiani et al (2021), Lu et al (2021), and Usman et al (2021) in America and Zhe et al (2021) in Europe. Completing the analysis of previous models, we found evidence of a bilateral causality between economic growth and financial development in Sub-Saharan Africa.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Inflation worsens the financial system as predicted by most theories. These findings are consistent with Lahiani et al (2021), Lu et al (2021), and Usman et al (2021) in America and Zhe et al (2021) in Europe. Completing the analysis of previous models, we found evidence of a bilateral causality between economic growth and financial development in Sub-Saharan Africa.…”
Section: Resultssupporting
confidence: 88%
“…Among the kinds of clean technologies, renewable energies (hydro, wind, solar, biomass, geothermal, ocean) constitute an inexhaustible energy resource, but to achieve the transformation, large-scale investments are crucial, therefore creating the theoretical investment-ecology-growth loop. Four hypotheses have been established: (i) the growth hypothesis stating that energy consumption through the production process improves economic growth (Odugbesan and Rjoub 2020; Zhe et al 2021;Usman et al 2021), (ii) the conservation hypothesis reporting that economic growth leads to an increase or decrease in energy demand (Gaies et al 2019;Shahbaz et al 2021), (iii) the feedback hypothesis formulating that there is a bidirectional causality between growth and energy consumption (Aimer 2020), (iv) and the neutrality hypothesis saying that there is no link (Maji et al 2019).…”
Section: Theoretical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the study revealed that financial inclusion is a significant agent of carbon mitigation in the 25th and 50th quantiles but the impact remained unexplainable in the last two quantiles (75th and 90th). Moreover, Usman et al (2021) checked for the role of renewable energy innovations and financial development in improving the ecological footprint amid other factors for the case of the United States by using the quarterly period 1985: Q1‐2014: Q4. Interestingly, the findings showed that the desirable environmental effect of financial development on ecological footprint only happens when threshold of development in the financial system is attained while such occurrence is not observed with the carbon dioxide model.…”
Section: Related Literature Reviewmentioning
confidence: 99%
“…For developing countries, they found a positive impact of remittances on household credit in the long term but no impact in the short term. In addition, following a sustainable development approach, other recent studies that have examined the link between remittancesrelated factors and environment quality (Qin et al, 2021;Zafar et al, 2021) and financial development (as a holistic proxy to capture all financial factors that include remittances) in an environmental framework (Kihombo et al, 2021;Usman et al, 2021;Wang et al, 2021). Specifically, Zafar et al (2021) explored the case of 22 world highest remittance-receiving countries to examine the link between remittances (as a proxy for financial development), export diversification, economic growth, education, energy variable, and carbon emission over the period 1986-2017.…”
Section: Related Literature Reviewmentioning
confidence: 99%